Changing patterns in the epidemiology and outcomes of inflammatory bowel disease in the United Kingdom: 2000‐2018. Issue 10 (1st April 2020) - King, Dominic; Reulen, Raoul C.; Thomas, Tom; Chandan, Joht Singh; Thayakaran, Rasiah; Subramanian, Anuradhaa; Gokhale, Krishna; Bhala, Neeraj; Nirantharakumar, Krishnarajah; Adderley, Nicola J.; Trudgill, Nigel
Summary: Background: Data regarding incidence, prevalence and long‐term outcomes of inflammatory bowel diseases in the UK are limited or outdated. Aims: To investigate incidence and prevalence of Crohn's disease and ulcerative colitis and risk of colorectal cancer and all‐cause mortality in these diseases. Methods: Inflammatory bowel disease cases between 2000 and 2018 were identified from a national primary care database. Inflammatory bowel disease prevalence was forecast until 2025. The association between inflammatory bowel disease and colorectal cancer and all‐cause mortality was investigated using age/sex‐matched retrospective cohort studies. Hazard ratios were adjusted for age, sex, deprivation, comorbidity, smoking status and body mass index. Results: Ulcerative colitis prevalence increased from 390 to 570 per 100 000 population from 2000 to 2017. Prevalence of Crohn's disease increased from 220 to 400 per 100 000. In 2017 male Crohn's disease prevalence was 0.35% (95% confidence interval 0.34‐0.36); female prevalence was 0.44% (0.43‐0.45). Prevalence of inflammatory bowel disease is predicted to be 1.1% by 2025. Incidence of ulcerative colitis and Crohn's disease was 23.2 (22.8‐23.6) and 14.3 (14.0‐14.7) per 100 000 person‐years respectively. Subjects with ulcerative colitis were more likely to develop colorectal cancer than controls (adjusted Hazard Ratio 1.40 [1.23‐1.59]). Colorectal cancer rates remained stable in inflammatory bowel diseases over time. Ulcerative colitis and Crohn's disease were associated with increased risk of all‐cause mortality (1.17 [1.14‐1.21] and 1.42 [1.36‐1.48] respectively). Conclusions: The UK prevalence of inflammatory bowel disease is greater than previous reports suggest and we predict an 11% increase in prevalence by the year 2025. Mortality risk in inflammatory bowel disease and colorectal cancer risk in ulcerative colitis are increased compared to matched controls.